THE EFFECT OF WORD WEBBING TECHNIQUE ON THE STUDENTS’ VOCABULARY MASTERY - Achmad Ramadhan; Siti Lutfiah Rabiyatul Adawiyah (UIN Sumatera Utara, 2020)
The objective of this study is to find out whether the students’ vocabulary mastery thaught by word webbing technique is better than without word webbing technique. The method of this research was quantitative with the experimental research design. The population of this study was the 48 students at seventh grade of SMP Swasta Galih Agung with two groups, experimental class consists of 21 students and control class consists of 27 students. The researchers taught the experimental class by using word webbing technique and control class taught without using word webbing technique. To collect the data the researchers used vocabulary test in multiple choice as the instrument. The post-test was given by the researchers aftergiving the treatment. The data were calculated by using t-test formula with the degree freedom (df) = 46 at the level of significance 0.05. it was found that tcount value was 10,491 and t table was 2,000. After analyzing the data, it was found that t count is higher than t table. It means that Ha is accepted and Ho is rejected. It can be concluded that the students’ vocabulary mastery taught by word webbing technique is better than without word webbing technique.